2008
DOI: 10.1088/0953-8984/20/39/395211
|View full text |Cite
|
Sign up to set email alerts
|

Single-crystal NMR for the layered semiconductor TlGaSe2

Abstract: We report on a 69Ga and 205Tl NMR study of single-crystal thallium gallium selenide. Our findings show that transformation from the high temperature paraelectric phase to the low temperature ferroelectric phase occurs via an incommensurate phase that exists in the temperature range from Tc = 107.5 to Ti = 118 K. On approaching phase transition at Ti from above, the crystal exhibits soft mode behavior, which is somewhat different for thallium and gallium substructures. Redistribution of 69Ga line intensitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 46 publications
0
9
0
5
Order By: Relevance
“…[22]. While no data exist in TlInS 2 so far, we expect that crystal has few absorption maxima across the layer depending on Tl-ion configurations since Tl atom (as well as In) in the F-phase has structurally inequivalent positions on a single unit cell [26]. We expect that excitons labeled A in Fig.…”
Section: Discussionmentioning
confidence: 90%
“…[22]. While no data exist in TlInS 2 so far, we expect that crystal has few absorption maxima across the layer depending on Tl-ion configurations since Tl atom (as well as In) in the F-phase has structurally inequivalent positions on a single unit cell [26]. We expect that excitons labeled A in Fig.…”
Section: Discussionmentioning
confidence: 90%
“…A large number of experimental findings. [10][11][12][13][14][15][16][17] indicated that in TlGaSe 2 , a sequence of structural phase transitions from paraphase to INC phase at T i $ 120 K and then to the commensurate (C) ferroelectric phase at T c $ 110 K were observed. Therefore, for a full discussion, the possible influence of the ferroelectric state on the observed phenomena should be discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the great number of publica tions on these crystals, their interest for researchers has not weakened. The results of studying the physical properties of compounds were recently analyzed in review [1]. As a rule, crystals of this family reveal both semiconductor and ferroelectric proper ties.…”
Section: Introductionmentioning
confidence: 99%